PELATIHAN TENIS TERHADAP GURU PENDIDIKAN JASMANI SEKOLAH DASAR NEGERI DI KOTA PADANG - Damrah, Damrah; Pitnawati, Pitnawati; Erianti, Erianti (Universitas Pendidikan Ganesha, 2019)
The issue of sports nursery is a very important issue to get national and international athletes, especially to get talented and quality tennis athletes. The purpose of this training is to get athletes in the field of sports through tennis training for physical education and physical education. The Physical Education teacher is the main source to help get talented students in sports including tennis. The method used in this activity is in the form of training given to physical and health physical education teachers who have the potential and desire to develop tennis in their respective elementary schools. Because there are relatively many primary schools in the city of Padang, the object of this study was conducted in the District of Tangah City, this is because the Koto area has adequate human resources and facilities to foster talented children. Thus the number of PJOK teachers involved in this training was 31 teachers and 62 students. From the results that have been carried out for one semester for the 2018/2019 school year are 1) 15 teachers (48%) PJOK who have the ability to foster and train children with adequate support facilities, namely support for infrastructure, school support and support the community. And 10 (31%) PJOK teachers who have the ability to foster and but do not have full support from schools and communities. The remaining 6 teachers (19%) still do not have the ability to develop tennis, but are ready to support this training program. 2) 56 students (90%) have talents and interests in tennis, while 6 other students (19%) still need to be given an understanding and understanding of the benefits of tennis.